Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/ncomms13078
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared exciton-polaritons in strongly coupled single-walled carbon nanotube microcavities

Abstract: Exciton-polaritons form upon strong coupling between electronic excitations of a material and photonic states of a surrounding microcavity. In organic semiconductors the special nature of excited states leads to particularly strong coupling and facilitates condensation of exciton-polaritons at room temperature, which may lead to electrically pumped organic polariton lasers. However, charge carrier mobility and photo-stability in currently used materials is limited and exciton-polariton emission so far has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
144
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 40 publications
7
144
0
Order By: Relevance
“…In particular, one-dimensional (1D) excitons in SWCNTs have enormous oscillator strengths, revealing a very large VRS exceeding 100 meV in microcavity devices containing a film of single-chirality SWCNTs (Graf et al, 2016); the VRS showed a g ∝ √ N behavior, where N is the number of dipoles (i.e., excitons in the present case), evidencing cooperative enhancement of light-matter coupling (Dicke, 1954;Zhang et al, 2016a), as shown in Fig. 25(a).…”
Section: Moreover Nanomaterials With Large Binding Energymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, one-dimensional (1D) excitons in SWCNTs have enormous oscillator strengths, revealing a very large VRS exceeding 100 meV in microcavity devices containing a film of single-chirality SWCNTs (Graf et al, 2016); the VRS showed a g ∝ √ N behavior, where N is the number of dipoles (i.e., excitons in the present case), evidencing cooperative enhancement of light-matter coupling (Dicke, 1954;Zhang et al, 2016a), as shown in Fig. 25(a).…”
Section: Moreover Nanomaterials With Large Binding Energymentioning
confidence: 99%
“…(a) Angleresolved reflectivity and photoluminescence spectra for (6,5) SWCNT microcavity exciton polaritons with increasing nanotube concentrations (from top to bottom) and increasing cavity thickness and detuning from (left to right). Adapted with permission from(Graf et al, 2016). (b) Transmittance spectra for a cavity containing aligned (6,5) SWCNTs at zero detuning for various polarization angles from 0 • to 90 • .…”
mentioning
confidence: 99%
“…Strong light–matter interactions have come into the spotlight in recent years, as a means of modifying molecular properties by tuning of their electromagnetic environment. The phenomenon has been demonstrated for organic/inorganic molecules, nanographene, monolayer transition metal dichalcogenides, proteins, chlorosomes, single‐wall carbon nanotubes, single molecules and even within living organisms . Applications of strongly coupled systems so far comprise polariton lasing and superfluidity, efficient second harmonic generation, room temperature Bose–Einstein condensates, conductivity enhancement and quantum information processing .…”
Section: Figurementioning
confidence: 99%
“…Below we demonstrate that this criterion can be met in experimentally realizable configurations, similar to those presented in recent experiments. [49][50][51] Our task is to evaluate the energy of the polariton states and to explore the conditions that will need to be achieved for the lower polariton to have an energy that is lower than that of the dark exciton. In what follows we outline our approach; we begin by discussing the dispersion of the polariton modes.…”
mentioning
confidence: 99%